Association of KISS1R gene polymorphism (rs397515615) with idiopathic female infertility in the northern of Iran - Peghah Yousefkhah; HamidReza Vaziri; Tooba Mirzapour (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Īlām)
Introduction:  Mutations in the KISS1R gene are among the most critical potential causes of infertility. This gene plays a role in the regulation of the hypothalamus-pituitary-gonadal (HPG) axis and is used in the regulation of reproductive cycles and maturation of humans. The present study aimed to investigate the relationship between the Gly56Ala genetic variation of the KISS1R gene and infertility in a population of women in northern Iran. Materials & Methods: In this work, among the women referred to Al-Zahrai Hospital of Rasht (Gilan Province, Iran) 100 women (50 infertile and 50 healthy) with age range (35.1 ± 2.1) were examined as patient and control group, respectively. Blood samples were collected with a volume of 2 ml and poured into EDTA carrier tubes. The DNA was extracted from leukocytes using a GPP kit. Allele-specific polymerase chain reaction (AS-PCR) was used to determine the genotype of KISSIR gene polymorphism (rs397515615). Results: The findings indicated that there was no significant correlation in genotype distribution between patients and control subjects in the samples evaluated in Gilan Province, Iran (P=0.216). Conclusion: The Gly56Ala polymorphism of the KISS1R gene is not related to an increase in the risk of female infertility in the population of Gilan Province, Iran. Moreover, this gene is not considered a risk factor for female infertility in northern Iran. The change in the sampling location or size makes it possible to obtain different results.